Penilaian Edukasi Bidan dan Kepatuhan Ibu Hamil melakukan Antenatal Care terhadap Pencegahan Preeklampsia - Sultina Sarita; Hasmia Naningsi; Nasrawati Nasrawati; Nirmawati Nirmawati (PT Karya Inovasi Berkelanjutan, 2026)
Introduction and Method Preeclampsia is a pregnancy complication that can lead to maternal and fetal morbidity and mortality. This condition is characterized by an increase in blood pressure accompanied by proteinuria occurring after 20 weeks of gestation. This study was a quantitative observational study with a cross-sectional design. The population consisted of 107 third-trimester pregnant women in the working area of BLUD UPTD Puskesmas Perumnas, Kendari City. A sample of 52 respondents was selected. Data was collected using questionnaires and analyzed using the Chi-square test. Result Among the 52 respondents, midwife education assessment was predominantly in the